2012
DOI: 10.1016/s0140-6736(12)61350-6
|View full text |Cite|
|
Sign up to set email alerts
|

Associations of kidney disease measures with mortality and end-stage renal disease in individuals with and without diabetes: a meta-analysis

Abstract: Background Chronic kidney disease is characterised by low estimated glomerular filtration rate (eGFR) and high albuminuria, and is associated with adverse outcomes. Whether these risks are modified by diabetes is unknown. Methods We did a meta-analysis of studies selected according to Chronic Kidney Disease Prognosis Consortium criteria. Data transfer and analyses were done between March, 2011, and June, 2012. We used Cox proportional hazards models to estimate the hazard ratios (HR) of mortality and end-sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
669
2
31

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 1,063 publications
(760 citation statements)
references
References 32 publications
25
669
2
31
Order By: Relevance
“…On the contrary, allcause mortality, not cardiovascular events, was strongly associated with reduced eGFR \30 ml/min per 1.73 m 2 in normoalbuminuric diabetic patients in this present study. Supporting this notion, hazard ratios for all-cause mortality as well as cardiovascular mortality increased in normoalbuminuric diabetic patients with low GFR [19]. The FIELD study also revealed that normoalbuminuric patients with eGFR 30-59 ml/min per 1.73 m 2 had a higher risk of cardiovascular events, cardiovascular death, non-coronary heart disease deaths, death from any cause than normoalbuminuric patients with eGFR C60 ml/min per 1.73 m 2 [7].…”
Section: \0001mentioning
confidence: 75%
“…On the contrary, allcause mortality, not cardiovascular events, was strongly associated with reduced eGFR \30 ml/min per 1.73 m 2 in normoalbuminuric diabetic patients in this present study. Supporting this notion, hazard ratios for all-cause mortality as well as cardiovascular mortality increased in normoalbuminuric diabetic patients with low GFR [19]. The FIELD study also revealed that normoalbuminuric patients with eGFR 30-59 ml/min per 1.73 m 2 had a higher risk of cardiovascular events, cardiovascular death, non-coronary heart disease deaths, death from any cause than normoalbuminuric patients with eGFR C60 ml/min per 1.73 m 2 [7].…”
Section: \0001mentioning
confidence: 75%
“…Previous studies have shown that low eGFR measured at a single time point is an important risk factor for ACM. 3,5,[17][18][19] We sought to evaluate whether prior change in eGFR contributes independently to ACM prognosis in the clinical setting, where last eGFR value is known. Previous studies have investigated this association from a clinical trial perspective, adjusting for the first eGFR.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 shows the multivariate-derived ESRD cumulative rates according to treatment type, patient age, diabetes, and hypertension, which, alongside year of surgery, were the most informative predictors of ESRD (Supplementary Table 1). ESRD is a life-threatening condition [4]. In young and healthy persons, the estimated risk of ESRD at 15 yr is 0.04% (95% CI, 0.008-0.09), reaching a peak of 0.3% (95% CI, 0.2-0.4) in healthy kidney donors [5].…”
mentioning
confidence: 99%